Computed tomography- and magnetic resonance imaging-based Bosniak Classification of Cystic Renal Masses Version 2019: a comprehensive review and comparison to version 2005 - Dróżdż, Tomasz; Zielińska, Katarzyna; Głuszek, Stanisław; Dopierała, Dawid; Kosowski, Marcin; Szpak, Rafał; Cieszanowski, Andrzej (Medical Studies/Studia Medyczne, 2021)
Cystic renal lesions are common findings on abdominal imaging studies. Bosniak Classification version 2005 and 2019 consists of five categories of cystic masses. The 2019 modification is more detailed and extensive compared to version 2005. The novelties in version 2019 are implementation of diameter values of cystic septa and walls as well as inclusion of magnetic resonance imaging for classification of cystic renal masses. The aim of our study was to review a new proposal for the assessment of renal cysts and review the results of studies which compared diagnostic performance and interobserver agreement of both versions from 2005 and 2019.